From Four Eyes to Divine Eyes: A Qur’anic Taqwā Governance Model for Islamic Finance - Supriadi, Edi (Jujurnal Publisher, 2025)
This study introduces the Divine Eyes Principle (DEP) as an innovative framework that integrates spiritual oversight into Islamic financial governance. Building upon the conventional Four Eyes Principle (FEP)—a risk control mechanism emphasizing dual authorization—the DEP advances the concept by embedding Qur’anic values of amanah (trust) and murāqabah (divine vigilance). Using a qualitative–normative approach through textual and comparative analysis of Islamic sources and governance literature, this research explores how divine consciousness enhances institutional accountability and moral integrity. Findings indicate that while the FEP ensures procedural control, the DEP establishes taqwā-based accountability that aligns managerial decisions with maqāṣid al-sharī‘ah. By transforming governance into an act of worship (‘ibādah), the DEP encourages sincerity, ethical transparency, and holistic responsibility among decision-makers. This framework contributes to the growing discourse on Islamic Corporate Governance by introducing a spiritually grounded paradigm that connects regulatory compliance with divine accountability. The DEP ultimately aims to cultivate integrity-driven financial institutions where performance is measured not only by efficiency but by adherence to divine trust.